"Брат застрелил митрополита в моем присутствии". Загадки біографії "родича" архімандрита Смарагда (Латишенка) - Стародуб, А.В. (Сiверянський літопис, 2021)
Мета статті – з’ясувати обставини засудження радянською каральною
системою особи, яка називала себе Антоном Івановичем Латишенком та
стверджувала, що є співучасником вбивства митрополита Варшавського Георгія (Ярошевського). До основних завдань публікації належать верифікація даних, які містяться в архівно-слідчій справі А. Латишенка, відтворення реальної
хронології подій, причинно-наслідкових зв’язків між ними, а також аналіз варіантів «автобіографій» фігуранта розслідування. Методологічною основою
публікації є культорологічно-соціологічна інтерпретація історичного феномену
«самозванства», зокрема – на основі підходів, запропонованих сучасним російським філософом Г. Тульчинським. Наукова новизна полягає в запроваджені до
наукового обігу та критичній інтерпретації виявлених архівних джерел. Висновки. З’ясовано, що інформація, яку у 1924–1926 рр. повідомляв про себе А. І. Латишенко, була абсолютно вигаданою, а радянські слідчі органи не лише
не змогли верифікувати більшість його тверджень, а й встановити особу перебіжчика з Польщі. Спростовано можливість причетності цієї особи до вбивства у Варшаві 8 лютого 1923 р. Поставлено під сумнів не тільки родинну спорідненість, але й навіть знайомство з архімандритом Смарагдом (Павлом Латишенком). Зроблено припущення щодо справжнього походження, рівня освіти та
роду занять авантюриста. The article clarifies the circumstances of the conviction by the Soviet punitive
system of a person who called himself Anton Ivanovich Latyshenko and claimed to be
an accomplice in the assassination of Warsaw Metropolitan George (Yaroshevsky). A
defector from Poland, who claimed to be a doctor by profession and a priest, told
several contradictory (and even mutually exclusive) versions of his biography from
December 1924 to April 1926. In an attempt to finally legalize himself in the USSR,
Latyshenko attracted the attention of the Joint State Political Directorate, was
arrested, and later sentenced to 3 years in prison in the Solovki prison campand to 3
years in exile in the Urals.
The author verified the data contained in the archival and investigative case of
A.Latyshenko, recreated the real chronology of events, established causal links
between them. Several variants of the «autobiographies» of the criminal investigation
participant were analyzed. A. Latyshenko's key statements are classified on the basis
of a philosophical and sociological approach to the interpretation of the historical
phenomenon of «impersonation». Hypothetical plans for further attempts to «convert»
the false stories of the adventurer into a certain status in Soviet society have been
reconstructed.
On the basis of archival sources introduced for the first time into scientific
circulation, the author made the following conclusions:
1. All the information that A.I. Latyshenko reported about himself in 1924-1926
was completely fictional.
2. The Soviet investigating authorities not only failed to verify most of his
allegations, but also failed to establish the true identity of the defector from Poland.
3. This person was not involved in the murder in Warsaw on February 8, 1923.
4. Not only family ties are doubtful, but even Anton Latyshenko’s acquaintance
with Archimandrite Smaragd (Pavel Latyshenko).
5. The imposter, most likely, did not come from the clergy, did not have a
professional medical education and the priesthood.